Assessing the Accessibility of Content for Geriatric Fellowship Programs. Issue 1 (29th November 2020) - Maybee, Camilla; Nguyen, Nam Tran; Chan, Melissa; Chan, Emily; Wei, Chapman; Quan, Theodore; Wei, Chaplin; Gu, Alex; Roth, Katalin E.
Abstract : The information available on program websites concerning geriatric fellowships in internal medicine and family medicine is a crucial factor in generating applicants' interest in individual programs. Our study aimed to quantify the accessibility and quality of information available on accredited geriatric (family medicine and internal medicine) fellowship program websites and further analyze the implications of the results obtained. A list of geriatric (family medicine and internal medicine) fellowship programs was analyzed through quantified measures after being verified for accreditation. Certain criteria were evaluated for each of these programs, such as website accessibility and whether critical information was available on online program websites. These criteria were centered on academic, administrative, and application‐based factors. Hundred and fifty eight Family Medicine and Internal Medicine geriatric fellowship programs were identified in total, of which only 150 were accredited by the Accreditation Council for Graduate Medical Education and considered for analysis. Of these, 20 (13.33%) programs had website links that were nonfunctional and only 145 programs had websites at all. On programs' websites, information regarding aspects such as contact information—including phone number or email for the program—were lacking. Other information regarding past and current fellows, research, and curriculum were also generally lacking. Geriatric Fellowship websites in Family Medicine and Internal Medicine can gain better traction from those interested in applying for their programs by updating information more often and providing more and better information concerning critical aspects of the programs themselves online.